1996
DOI: 10.1111/j.1476-5381.1996.tb15478.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclopiazonic acid and thapsigargin on electromechanical activities and intracellular Ca2+ in smooth muscle of carotid artery of hypertensive rats

Abstract: 1 The effects of cyclopiazonic acid (CPA) and thapsigargin (TG), both of which are known to inhibit sarcoplasmic reticular Ca2+-ATPase, on the mechanical activities, intracellular Ca2+ level and electrical activities of smooth muscle of the carotid artery of stroke-prone spontaneously hypertensive rats (SHRSP) and Wistar Kyoto rats (WKY) were compared. 2 Both CPA and TG induced elevation of tension of the smooth muscle, which was composed of a phasic and a tonic component. The level of tension attained, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…The activation of ␣ 1 -adrenoceptors causes phospholipase C-mediated hydrolysis of the membrane phospholipid, phosphatidylinositol 4,5-bisphosphate, yielding two second messengers, inositol 1,4,5-trisphosphate (IP 3 ) and diacylglycerol (6,21,23). IP 3 binds to receptors located on the sarcoplasmic reticulum and releases stored Ca 2ϩ (11,23), which is responsible for the transient contractile response to phenylephrine that was observed in rat aortic rings incubated in Ca 2ϩ -free solution.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of ␣ 1 -adrenoceptors causes phospholipase C-mediated hydrolysis of the membrane phospholipid, phosphatidylinositol 4,5-bisphosphate, yielding two second messengers, inositol 1,4,5-trisphosphate (IP 3 ) and diacylglycerol (6,21,23). IP 3 binds to receptors located on the sarcoplasmic reticulum and releases stored Ca 2ϩ (11,23), which is responsible for the transient contractile response to phenylephrine that was observed in rat aortic rings incubated in Ca 2ϩ -free solution.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane potential was recorded intracellularly using a glass capillary microelectrode (tip resistance, 40-80 MΩ) filled with 3M KCl, as previously described (Sekiguchi et al, 1996). The reference electrode was an Ag-AgCl plate.…”
Section: Membrane Potential Recordingmentioning
confidence: 99%
“…We have reported that the endotheliumCorrespondence to: K. Shimamura, Department of Clinical Pharmacology, Faculty of Pharmaceutical Sciences, Health Science University of Hokkaido, Kanazawa 1757, Ishikari-Tobetsu, Hokkaido 061-0293, Japan Phone: +81-1332-3-1211 ext.3160 Fax: +81-1332-3-1669 e-mail: shimamu@hoku-iryo-u.ac.jp removed carotid artery of stroke-prone spontaneously hypertensive rats (SHRSP) contracts spontaneously with an increase in intracellular free Ca 2+ concentration (Sekiguchi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…We conclude that the SHR carotid artery has an increased total capacity of SR for purpose of Ca 2 The results that the contractile responses to CPA and thapsigargin were inhibited by nifedipine may suggest that Ltype Ca 2 channels are directly activated by these agents. Although such a direct action has never been reported, Sekiguchi et al (17) reported that CPA depolarized the smooth muscle membrane of the carotid arteries, probably due to an inhibition of Ca 2 -activated K channels via the depletion of SR Ca 2 and/or an activation of nonspecific cation channels. However, in the present study, the following findings provided no support for the idea that CPA has a membrane depolarizing effect: 1) after a 5-min incubation with 45 Ca, CPA decreased the basal Ca 2 influx; and 2) SR Ca 2 was not depleted during the addition of CPA.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that, even in the resting state, the carotid artery of SHR shows greater levels of Ca 2 influx and [Ca 2 ]i than the carotid artery of normotensive WistarKyoto rats (WKY) (15,16). To compensate for the increased level of [Ca 2 ]i in this artery, Ca 2 that enters the cells is likely to be taken up into the SR, because the addition of CPA or thapsigargin caused a larger contraction in SHR than in WKY (17). This further suggests that the Ca 2 uptake function of the SR during rest in the carotid artery is increased in SHR compared with WKY.…”
Section: Introductionmentioning
confidence: 99%